2020
DOI: 10.1161/circep.119.007925
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cardiac Resynchronization Therapy on Heart Transplant-Free Survival in Pediatric and Congenital Heart Disease Patients

Abstract: Background - Cardiac resynchronization therapy (CRT) studies in pediatric and/or congenital heart disease (CHD) patients have shown an improvement in ejection fraction and heart failure symptoms. However, a survival benefit of CRT in this population has not been established. This study aimed to evaluate the impact of CRT upon heart transplant-free survival in pediatric and CHD patients, using a propensity score-matched analysis. Methods - This single-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 15 publications
2
15
0
Order By: Relevance
“…Patients with a systemic LV have shown the greatest response to CRT in comparison to systemic RV and single-ventricle patients. 401,403,411 While the majority of studies of CHD and CRT have found improvements in EF, clinical status, and QRS duration, only recently has a survival benefit been shown. 401 Additional considerations for use of CRT in these populations include the need to normalize QRS duration for age by the use of z scores 422 ; the need for varied approaches to device implantation based on size, access, and anatomy; and the potential for disadvantages of size to outweigh procedural benefits in the smallest of patients.…”
Section: Synopsismentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with a systemic LV have shown the greatest response to CRT in comparison to systemic RV and single-ventricle patients. 401,403,411 While the majority of studies of CHD and CRT have found improvements in EF, clinical status, and QRS duration, only recently has a survival benefit been shown. 401 Additional considerations for use of CRT in these populations include the need to normalize QRS duration for age by the use of z scores 422 ; the need for varied approaches to device implantation based on size, access, and anatomy; and the potential for disadvantages of size to outweigh procedural benefits in the smallest of patients.…”
Section: Synopsismentioning
confidence: 99%
“…CRT has been used in these patients with varying degrees of success. Patients with a systemic LV have shown the greatest response to CRT in comparison to systemic RV and single‐ventricle patients 401,403,411 . While the majority of studies of CHD and CRT have found improvements in EF, clinical status, and QRS duration, only recently has a survival benefit been shown 401 …”
Section: Section 7 Congenital Heart Disease and Pediatric Populationsmentioning
confidence: 99%
“…Pediatric and CHD patients are at risk of cardiomyopathy either secondary to long-term pacing or cardiac dyssynchrony, secondary to existing conventional (single-site, non-CSP) pacing or inherent conduction disease. Traditional biventricular pacing (CRT) has been used with some success in these scenarios (Chubb et al, 2020), but there is growing interest in CSP both to treat and prevent this issue.…”
Section: Indications For Conduction System Pacingmentioning
confidence: 99%
“…Additionally, the identification of echocardiographic parameters that may identify Fontan patients who would benefit from CRT is paramount to gaining the maximal benefit from this therapy. A recent publication on outcome on CRT treated patients with congenital heart disease, including 9 patients with UVH and propensity matched controls shows promising effect of CRT treatment, leading to improved transplant-free survival [40].…”
Section: Clinical Implicationmentioning
confidence: 99%